2017
DOI: 10.1038/s41598-017-00342-1
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylethanolamide induces microglia changes associated with increased migration and phagocytic activity: involvement of the CB2 receptor

Abstract: The endogenous fatty acid amide palmitoylethanolamide (PEA) has been shown to exert anti-inflammatory actions mainly through inhibition of the release of pro-inflammatory molecules from mast cells, monocytes and macrophages. Indirect activation of the endocannabinoid (eCB) system is among the several mechanisms of action that have been proposed to underlie the different effects of PEA in vivo. In this study, we used cultured rat microglia and human macrophages to evaluate whether PEA affects eCB signaling. PEA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(93 citation statements)
references
References 63 publications
2
90
0
1
Order By: Relevance
“…PEA, as an endogenous compound, has a double therapeutic effect (that is, anti-nociceptive and anti-inflammatory) without adverse effects at pharmacologically relevant doses [10, 11]. Recent report highlights a new PEA potential mechanism of action mediated by the induction of the CB2 up-regulation [12]. The large particle size and lipidic nature of PEA limit its solubility and bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…PEA, as an endogenous compound, has a double therapeutic effect (that is, anti-nociceptive and anti-inflammatory) without adverse effects at pharmacologically relevant doses [10, 11]. Recent report highlights a new PEA potential mechanism of action mediated by the induction of the CB2 up-regulation [12]. The large particle size and lipidic nature of PEA limit its solubility and bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…Microglial cell migration is associated with neuroinflammation. Specifically, microglial migration and the related phagocytic activity can be activated by G-coupled receptors, which include chemokines ( Guida et al, 2017 ). A recent study demonstrated that the chemokine CCL2 modulates microglial cell migration through the MEK/ERK and PI3K pathways ( Bose et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although microglia express a wide range of lipid‐sensitive receptors and lipid metabolism‐related genes (Mauerer, Walczak, & Langmann, ; Mecha et al, ), the molecular link between bioactive fatty acids and their effects in microglia has not been completely clarified yet. Emerging evidence suggests that PUFAs can drive a protective phenotype through the activation of CB2, which is among microglial receptors reprogramming microglia toward beneficial function (Guida et al, ; Mecha et al, ; Nunez et al, ) but other receptors may be involved including ALX/FPR2 receptors (Bisicchia et al, ) (Figure ).…”
Section: Alimentary Components Driving Pro‐regenerative Microglia Funmentioning
confidence: 99%
“…Although microglia express a wide range of lipidsensitive receptors and lipid metabolism-related genes (Mauerer, Walczak, & Langmann, 2009;Mecha et al, 2015), the molecular link between bioactive fatty acids and their effects in microglia has not been completely clarified yet. Emerging evidence suggests that PUFAs can drive a protective phenotype through the activation of CB2, which is among microglial receptors reprogramming microglia toward beneficial function (Guida et al, 2017;Mecha et al, 2015;Nunez et al, 2004) (Ghosh et al, 2017), also dietary lipids may likely shape microglia phenotype acting on cell metabolism. In support to this hypothesis, fasting and ketogenic diet, that lead to a sustained reduction in blood glucose levels and to an increase in circulating ketones, have been reported to have anti-inflammatory actions and suppress activation of microglia by regulating their metabolic features (Longo & Mattson, 2014).…”
Section: Molecular Mechanisms Linking Receptor/channel Activation Tmentioning
confidence: 99%